Supplier Performance Prioritization Using Analytical Hierarchy Process Framework: Penentuan Prioritas Kinerja Pemasok Menggunakan Kerangka Kerja Proses Hierarki Analitis - Rachmawan, Yoga; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Supplier evaluation is a critical component of supply chain management to ensure operational continuity and procurement quality. Specific Background: Organizations require structured decision-making tools to assess multiple criteria in selecting and evaluating suppliers objectively. Knowledge Gap: Although the Analytical Hierarchy Process (AHP) has been widely applied, its structured implementation for supplier performance prioritization in the observed company context has not been systematically documented. Aims: This study aims to determine priority criteria and identify the best supplier alternative using the AHP framework. Results: The analysis produced weighted criteria rankings, verified consistency ratios below the acceptable threshold, and generated a final supplier priority order based on global weights. Novelty: The study presents a comprehensive hierarchical structuring of criteria and sub-criteria aligned with company-specific procurement conditions. Implications: The findings provide a structured decision support basis for managerial policy in supplier selection and contribute to applied research in supplier performance measurement using multi-criteria decision-making methods. Keywords: Analytical Hierarchy Process, Supplier Evaluation, Multi-Criteria Decision Making, Supply Chain Management, Decision Support System Key Findings Highlights Criteria weighting identified dominant factors in supplier assessment. Consistency ratio confirmed reliable pairwise comparison judgments. Final ranking determined a priority supplier based on global synthesis weights.